Transformasi Demitologi dalam Layanan Sosial Dakwah: Studi Etnografi Empat Kiai di Pulau Jawa - Huda, Sokhi; Bustomi, Abu Amar (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This article is a report on ethnographic research regarding the social da'wah services of four religious figures, namely Kiai Ghofur, Gus Samsudin, Gus Idris, and Ustadz Ujang Busthomi. The study focuses on analyzing the process of demythologization in the social da'wah services they provide, particularly concerning the integration of religion, rationality, and the needs of modern society. The results indicate a shift from magical elements to a more rational approach in their social da'wah services, integrating religious literacy and faith-moral therapy with social, economic, and health solutions. These kiai emphasize the relevance of religion to the needs of modern society, the strengthening of social cohesion, and the importance of responding to contemporary challenges. This study identifies four main themes: the transformation of religious practices, the integration of social needs and the community, inclusivity and egalitarianism in social services, and social empowerment and stability.